2016
DOI: 10.1590/1676-0611-bn-2014-0106
|View full text |Cite
|
Sign up to set email alerts
|

Cultural keystone species of fauna as a method for assessing conservation priorities in a Protected Area of the Brazilian semiarid

Abstract: The Cultural Keystone Species (CKS) method of identification has been used to define culturally important species. The objective of this study was to identify and characterize CKS vertebrates in the communities surrounding the Environmental Protection Area of Chapada do Araripe and define conservation priorities using semi-structured interviews and free listings. Interviews were conducted with 246 people; 53 species were identified and then included in categories of use: food, medicinal, handicraft and symboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
1
6
0
6
Order By: Relevance
“…The inventory-interview analysis of the sampling trace elements method and the use value calculation indicate the Common deer ( M. gouazoubira ) as possibly the most abundant species (common) in this Protected Area, corroborating found by Bonifácio et al [ 84 , 85 ]. M. gouazoubira is well adapted to semi-arid region and is widely distributed in this region [ 88 ].The forest fragments included in Forested Savannah vegetation and the transition area Rainforest/Savannah were the most used environments, both by M. gouazoubira and most of the species confirmed by evidence.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The inventory-interview analysis of the sampling trace elements method and the use value calculation indicate the Common deer ( M. gouazoubira ) as possibly the most abundant species (common) in this Protected Area, corroborating found by Bonifácio et al [ 84 , 85 ]. M. gouazoubira is well adapted to semi-arid region and is widely distributed in this region [ 88 ].The forest fragments included in Forested Savannah vegetation and the transition area Rainforest/Savannah were the most used environments, both by M. gouazoubira and most of the species confirmed by evidence.…”
Section: Discussionsupporting
confidence: 83%
“…These results indicate the representative role of the Common deer ( M. gouazoubira ) in the local context, which added to its likely availability in the environment, infers on the local knowledge of this species, which is being passed on in a similar way between the people of the studied groups. Bonifácio et al [ 84 , 85 ] studied communities from Chapada do Araripe (Ceará, Brazil) founded that M. gouazoubira is recognized as part of the local culture, not only as a food source for survival, but as embedded element to social practice, making this remarkable animal and very popular for local people. In the Bonifácio et al [ 85 ] study thirty-five respondents (100 %) stated that the reason for M. gouazoubira hunting in Araripe region in the past and/or present, was (is) the preference for its meat, which confirms that this species is one of the main huntable species of the semiarid region, which its meat is indicated as tasty and smooth for those who hunt it [ 88 ].The diversity of uses that M. gouazoubira can provide, especially for food and medicine, is a pattern made evident in many etnozoological studies, confirming the great cultural importance of this species as a resource in other rural communities of the neotropical zones [ 54 , 80 , 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…), for instance, are used as ingredients in popular medicines in Argentina, Bolivia, and other regions of Brazil [ 19 , 64 , 65 ]. Indeed, Bonifácio et al [ 66 ] recently suggested that Salvator merianae is the major medicinal species for semiarid areas in Brazil. The results reported by these authors reinforce previous investigations about the use of wild fauna-based remedies in areas of Caatinga in Northeast Brazil (e.g., [ 4 , 19 , 67 ]), and highlight the popularity of this species as a medicinal resource in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Na Área de Proteção Ambiental (APA) Chapada do Araripe, Nordeste do Brasil, M. gouazoubira é reconhecida como parte constitutiva da cultura local, não como fonte de alimento para a sobrevivência, mas como elemento incorporado à prática social, motivo pelo qual as inter-relações das comunidades locais com essa espécie são mantidas na região do Araripe (BONIFÁCIO;FREIRE;SCHIAVETTI, 2016;MELO et al, 2014).…”
Section: Introductionunclassified